Manoeuvring barriers: Assessing adaptive strategies for and persistent barriers to urban Nature-based Solutions in Lilongwe, Malawi - Bauer, Willi; Titz, Alexandra (Nature-Based Solutions, 2025)
Urban Nature-based Solutions (NbS) are increasingly promoted globally as a multifunctional and cost-effective way to address social and environmental challenges in cities. Based on these premises, there is a growing municipal interest in promoting NbS in cities of the so-called 'Global South'. However, current research is still clearly biased towards the 'Global North', with particularly few studies focusing on cities in Sub-Saharan Africa (SSA). As a result of these research gaps, there is a high risk that maladapted NbS – modelled on examples from other regions that do not meet local requirements and needs – will be adopted. Against this background, this article examines barriers to the adoption of urban Nature-based Solutions and the opportunities for successful implementation of NbS in cities in Malawi. Drawing on qualitative data (workshops, narrative expert interviews, group discussions) collected during five research stays in Lilongwe (2022–2024), the article outlines and analyses in detail the strategies employed to overcome these barriers by those actors in charge for implementing the Lilongwe Ecological Corridor Initiative (LECI), a large-scale NbS in the country's capital city. By empirically exploring the particularities of the implementation of the LECI, the article characterises features of NbS in SSA rarely explored in other contexts, such as the reframing of existing greenspaces, the pragmatic adaptation of NbS-plans and the formulation of by-laws as part of their planning. These insights can serve as a basis for further conceptual developments and critical engagement and to promote a deeper understanding of the potentials and pitfalls of implementation strategies seeking to manoeuvre persistent barriers.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Adaptive strategies; Barriers; Lilongwe Ecological corridor initiative; Malawi; Nature-based Solutions; Urban greening